Validação de instrumento para a sistematização da assistência de enfermagem a crianças hospitalizadas de 0 a 5 anos - Ferreira, Thalys Maynnard Costa (2019)
The nursing process is considered an important tool with regard to the approach of the professional responsible for care to the being that requires its care actions. Therefore, the use of instruments that enable behaviors for the operationalization of nursing process in daily life has been the aim of studies in the methodological field. Objective: to analyze the process of validation and stratification of medical care risk of a data collection instrument focused on the nursing care systematization for hospitalized children aged 0 to 5 years. Method: methodological study, with quantitative approach, performed with 150 children in a pediatric clinic of a teaching hospital. In order to collect data, we complied with the stages for the validation of the content; clinical validation of the instrument and association of basic human needs and medical diagnoses. In order to analyze data, we used the calculation of content validity index and Kappa agreement analysis. In order to follow the validation, we applied the variance analysis followed by the K-means test (Cluster Analysis) and the Tuckey Test, as well as the binary classification descriptive model – WoE and grouping analysis, as well as descriptive statistics techniques. The research project was approved under CAAE protocol 76649517.3.0000.5183. Results: under a content validity index of 0.94, Kappa 0.71, according to the experts’ suggestions, 81.9%, besides the validity of the measurable establishment of clinical characteristics and health care risk of hospitalized children and a positive association between altered human needs and diagnoses, we can consider that the instrument is valid for applicability. Conclusion: the validation of the instrument was intended to provide care for children aged 0 to 5, thereby highlighting the growing need for the creation and improvement of valid instruments offered to health services.